One-pot synthesis of SnO2 nanoparticles decorated multi-walled carbon nanotubes using pulsed laser ablation for photocatalytic applications. (January 2023) - Al Baroot, Abbad; Elsayed, Khaled A.; Haladu, Shamsuddeen A.; Magami, Saminu Musa; Alheshibri, Muidh; Ercan, Filiz; Çevik, Emre; Akhtar, Sultan; A.Manda, Abdullah; Kayed, T.S.; Altamimi, Nafala A.; Alsanea, Aamerah A.; et al.
Highlights: Synthesis of SnO2 /CNT nanocomposite by laser ablation in an aqueous medium. Studying the optical, morphological, and crystallographic characterizations of the nanocomposites. SnO2 /CNT 10% is leading to 94% removal of the MB dye in 60 min of UV irradiation. Abstract: This work reports the synthesis and characterization of SnO2 /CNT nanocomposites and their photocatalytic performance. The nanocomposite catalysts were assembled via a pulsed laser ablation technique. Characterization was then undertaken by employing transmission electron microscopy (TEM), scanning electron microscopy (SEM), powder X-ray diffraction (XRD), and ultraviolet–visible spectroscopy. The photocatalytic activities of the SnO2 /CNT nanocomposite variants were studied based on the photodegradation of the methylene blue dye (MB). In this, the kinetics and mechanisms of the photocatalytic reactions were evaluated. The results from the various analyses were all correlated in confirming the composition, the incorporation of the dopant species and the structure of the nanocomposite catalysts. In particular, the crystallite sizes in the SnO2 and the fabricated SnO2 - CNT 5 % and SnO2 -CNT 10 % materials were confirmed as 26.40 nm, 30.90 nm, and 28.69 nm, respectively. The UV light-induced photocatalytic reactions were rapid, leading to 94 % removal of the MB dye in 60 min and 120 min of UV irradiation, in the presence of the SnO2 -CNT 10 % and the SnO2 -CNT 5 %, respectively. The overall reactions follow pseudo-first order kinetics, yielding rate constants of 2.82 × 10 −2 min −1 and 4.24 × 10 −2 min −1, for the SnO2 -CNT 5 % and the SnO2 -CNT 10 % photocatalyzed reactions, respectively. The overall findings of this work demonstrate the effectiveness of laser-based synthesized SnO2 -CNT nanocomposites in the UV light-induced degradation of the MB dye pollutant and show a potential application for the removal of a wide range of other dyes from wastewater.